2017
DOI: 10.1007/s00266-017-0812-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Patient-Reported Outcome Measures Following Transsexual Surgery

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“… 5 Concepts that are used to operationalize subjective evaluation (also called patient-reported outcomes, although transgender individuals are generally not referred to as “patients”) include treatment satisfaction, body image, self-esteem, life evaluations, happiness, and sexual function. 6 …”
mentioning
confidence: 99%
“… 5 Concepts that are used to operationalize subjective evaluation (also called patient-reported outcomes, although transgender individuals are generally not referred to as “patients”) include treatment satisfaction, body image, self-esteem, life evaluations, happiness, and sexual function. 6 …”
mentioning
confidence: 99%
“…An interview guide (see box 1 ) will be used to guide the interviews. Topics included in the guide were informed by PROMs reviewed in two recent systematic reviews of outcomes following gender-affirming treatments, 9 10 and other phase I plastic surgery-specific PROM development studies performed by our team. The qualitative interviewer will dynamically adapt the interview as needed (eg, for younger participants) to avoid asking irrelevant questions or questions that might be too personal for some to discuss (eg, sexual well-being).…”
Section: Methods and Analysismentioning
confidence: 99%
“…This barrier was highlighted in two recent systematic reviews, both of which identified that existing PROMs used in transgender surgery research are inadequate and called for new measures to be developed. 9 10 The development of a specific PROM is crucial because how someone feels and functions before and after gender-affirming treatments are concepts best assessed by self-report. 11 Furthermore, outcomes of treatments to alleviate feelings of gender incongruence are not measured by generic PROMs, including the 36-Item Short Form Health Survey, 12 which have been used to study gender-affirming surgery.…”
Section: Introductionmentioning
confidence: 99%
“…12 Despite their increasing use, there is a paucity of psychometrically robust PROMs as demonstrated by a number of systematic reviews. [13][14][15][16] This is particularly important if treatment decisions, study outcomes or adverse event reporting are to be based on their results. Psychometric validation of a PROM is complex, testing the questionnaire and its individual items for validity, reliability, responsiveness to change and clinical meaning.…”
Section: Introductionmentioning
confidence: 99%